Treatment Innovation in Orthopedic Surgery: A Case Study from Hospital for Special Surgery. Issue 2 (June 2018) - Waldman, Seth A.; Schottenfeld, Joseph R.; Gluck, Abbe R.
Excessive prescribing of pain medications after surgery has contributed to the epidemic of opioid misuse and diversion in the United States. Pain specialists may be particularly well situated to address these issues. We describe an attempt to reverse the trend at an orthopedic surgical hospital by implementing a peri-operative assessment and treatment service which minimizes preoperative opioid use, when necessary implements addiction treatment, and encourages early tapering from opioids.